Implanta????o de ERP em uma institui????o hospitalar: desafios e mudan??as necess??rias - Nunes, Elisangela dos Santos (2016)
Aiming at identifying the challenges and necessary changes when implementing ERP (Enterprise Resource Planning) software in hospital environments, as well as at minimizing future user insecurities toward the system, this paper accompanied the implementation process of an ERP from the alignment of operational processes all the way through to the delivery of a working tool suitable for all different areas of the hospital selected. Usually, upon deciding to acquire a system to automate certain operational processes, a client deals with insecurities toward the chosen tool???s assertiveness, the processes being modeled and the interactive capabilities for both internal and external clients. Asides from this and other such challenges, this study seeks to identify which changes are necessary to insure the implementation occurs with minimal issue, impacting administrative and assistance operations positively, as well as having all hired modules be implemented fully and successfully. Applying the research-action methodology allowed for the identification of the different stages of implementation, and for the details of the necessary changes to be made as the project advances (initially not accounted for in the scope of this paper) ??? these can be sited among other such less successful actions taken during the planning, controlling and finalizing stages of this project. The model offered here is suitable to hospitals that face difficulties in identifying requirements in adhering and implementation stages that are necessary for the delivery of a fully installed, working tool that can be used by trained professionals able to operate all acquired modules. Results show that, upon identifying and mitigating risks surrounding the key success aspects of such an implementation process as well as the necessary changes to operations and area management, the company is presented with improvement opportunities to corporate communications, better direction to information flow, better access to real time data and better integration of the different areas of the hospital, as well as potential new models for operational processes that, together, have the ability to create a more flexible and dynamic structure for future decision making processes.